2021
DOI: 10.1016/j.aquaculture.2020.735788
|View full text |Cite
|
Sign up to set email alerts
|

Purple bacteria as added-value protein ingredient in shrimp feed: Penaeus vannamei growth performance, and tolerance against Vibrio and ammonia stress

Abstract: White spot syndrome virus (WSSV) is an extremely destructive virus in shrimp farming which has caused a serious economic loss to global shrimp industry. Learning its infection routes is the basis for WSSV prevention and control. The digestive tract and gill were generally considered to be the target tissues for WSSV entry into shrimp. However, whether there is any other target tissue for WSSV entry into the shrimp is still not clear. In the present study, we firstly found that the transcripts of WSSV could be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 73 publications
0
39
0
Order By: Relevance
“…Three types of microbial fertilizers are generally considered for microbial fertilizer production on secondary resources: (i) a consortium of aerobic heterotrophic bacteria (AHB); [ 22 ], (ii) photoautotrophic microalgae (MA); [ 23 , 24 ] and (iii) photoheterotrophic purple non-sulfur bacteria (PNSB); [ 17 , 18 , 25 , 26 ]. AHB are probably the most widely applied and explored microbial fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Three types of microbial fertilizers are generally considered for microbial fertilizer production on secondary resources: (i) a consortium of aerobic heterotrophic bacteria (AHB); [ 22 ], (ii) photoautotrophic microalgae (MA); [ 23 , 24 ] and (iii) photoheterotrophic purple non-sulfur bacteria (PNSB); [ 17 , 18 , 25 , 26 ]. AHB are probably the most widely applied and explored microbial fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…The biomass of PNSB is appealing with a high protein content (40-61 g protein 100 g − 1 TSS), an outstanding protein quality (appealing profile EAA) and vitamins such as B1, B2, B3, B5, B6, B9, E and biotin (Sasaki et al, 1998). PNSB are studied as a feed ingredient, yet they are unique due to their addedvalue properties beyond the nutritional content: (i) they enhance the growth performance of several fish species and shrimp (Alloul et al, 2021;Chowdhury et al, 2016;Delamare-Deboutteville et al, 2019;Noparatnaraporn et al, 1987;Shapawi et al, 2012), (ii) have antimicrobial properties against shrimp Vibrio pathogens as demonstrated by our previous work (Alloul et al, 2021), (iii) contain antioxidants such as carotenoids (Sasaki et al, 1998) and (iv) can have color benefits for aquaculture animals (Noparatnaraporn et al, 1987). These bacteria can also serve as an astronaut food ingredient in regenerative life-support systems (Clauwaert et al, 2017) and live or dried PNSB have added value in crop production (Spanoghe et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Since PNSB possess versatile metabolic pathways, they are attractive candidates for multiple industrial applications. For example, they are broadly applied in the fisheries industry [35] and livestock industry, in bioremediation for sewage and heavy metals [36,37] and in the production of biofuels (photohydrogen or electricity) [38,39].…”
Section: Introductionmentioning
confidence: 99%